PTSD Among Healthcare Workers During the COVID-19 Outbreak: A Study Raises Concern for Non-medical Staff in Low-Risk Areas - Zhang, Ruike; Hou, Tianya; Kong, Xiangyu; Wang, Guibin; Wang, Hao; Xu, Shuyu; Xu, Jingzhou; He, Jingwen; Xiao, Lei; Wang, Yajing; Du, Jing; Huang, Yujia; et al. (Frontiers in Psychiatry, 2021)
Objective To investigate the prevalence of sleep quality and Post-traumatic stress disorder (PTSD) symptoms of Healthcare workers (HCWs) and identify the determinants for PTSD symptoms among high-risk and low-risk HCWs during the COVID-19 outbreak in China. Method The Pittsburgh Sleep Quality Index, and the Impact of Event Scale were used to assess sleep quality, and symptoms of PTSD of 421 Chinese HCWs, respectively, from 30 Jan to 2 March, 2020. The influencing factors of PTSD symptoms were identified by univariate analysis and multiple regression. Result The incidence rates of HCWs getting PTSD symptoms were 13.9%, respectively. High-risk HCWs had significantly poorer sleep quality(P=0.019). Poor sleep quality was the risk factor of PTSD symptoms both for high-risk HCWs and low-risk HCWs (P<0.001). Furthermore, non-medical staff were found to be the risk factor of PTSD symptoms only in low-risk area. Discussion HCWs in Hubei had poorer sleep quality. Low-risk non-medical HCWs were associated with more severe PTSD symptoms. Mental health programs should be considered for HCWs especially those who were often overlooked.